Cisplatin chemotherapy impairs the peri-implant bone repair around titanium implants: An in vivo study in rats - Matheus, Henrique Rinaldi [UNESP]; Ervolino, Edilson [UNESP]; Faleiros, Paula Lazilha [UNESP]; Novaes, Vivian Cristina Noronha [UNESP]; Theodoro, Letícia Helena [UNESP]; Garcia, Valdir Gouveia [UNESP]; Almeida, Juliano Milanezi de [UNESP] (Wiley, 2018)
Aim: The purpose of this study in animals was to evaluate the peri-implant bone repair against systemic administration of the antineoplastic agent. Material and methods: We used 84 male rats (Rattus norvegicus, albinus, Wistar), divided into two groups: cisplatin (CIS) and saline solution (SS). The titanium implants were inserted into the right tibia at day 0 in all animals from both groups. Group SS received SS intraperitoneally at 15 and 17 days postoperatively. Group CIS received 5 and 2.5 mg/kg of CIS intraperitoneally at 15 and 17 days postoperatively, respectively. Euthanasia was performed at 22, 30 and 60 days postoperatively. Twenty-four undecalcified specimens were prepared for histometric analysis of bone/implant contact (BIC). Sixty specimens were selected to bone area (BA) measurement, histological analysis and immunohistochemical analysis of RUNX-2, osteocalcin (OCN) and tartrate-resistant acid phosphatase (TRAP). BIC and BA were considered to be the primary outcome parameters. Results: Group CIS showed lower BIC (11.87 ± 0.97 mm; 19.19 ± 0.8 mm; 17.69 ± 1.05 mm; p ≤.05) and BA (3.68 ± 1.29 mm2; 3.05 ± 0.88 mm2; 3.23 ± 0.67 mm2; p ≤.05), as well as decreased number of RUNX-2 (102.8 ± 27.35 cells/mm2; 100.04 ± 8.61 cells/mm2; 118.82 ± 21.38 cells/mm2; p ≤.05)- and OCN-positive cells (120 ± 24.5 cells/mm2; 102 ± 27.73 cells/mm2; 100 ± 14.23 cells/mm2; p ≤.05) at 22, 30 and 60 days, respectively. The animals in group CIS also showed increased number of TRAP-positive cells (86.8 ± 6.37 cells/mm2; 71.5 ± 4.72 cells/mm2; 92.8 ± 9.52 cells/mm2; p ≤.05) and a persistent and exacerbated inflammatory response in all experimental periods. Conclusion: Within the limits of this study, it was concluded that the chemotherapeutic CIS negatively affects the bone repair at peri-implant areas, jeopardizing the osseointegration of titanium implants.
Keywords: antineoplastic agents; bone repair; chemotherapy; dental implants; osseointegration